Thermosensing Enlightened. (March 2017) - Delker, Carolin; van Zanten, Martijn; Quint, Marcel
Abstract : Understanding the molecular networks driving plant responses to high ambient temperatures is crucial for developing crop cultivars resistant to global warming. Although several factors involved in temperature signalling are known, a thermosensing mechanism had remained elusive. However, two recent publications demonstrate that the photoreceptor phytochrome B (phyB) also acts as a thermosensor.